Seychelles : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
On the revenue side of Seychelles, both tax and nontax revenues have shown marked increases during 1998-99 on account of a number of factors. A strengthening of tax administration has yielded significant improvements in tax collections, particularly in the areas of taxes on income and profits, which has increased from 4.4 percent of GDP in 1997 to 6.8 percent of GDP in 1999. Trade taxes on domestic goods and services have grown from about 7 percent of GDP in 1997 to about 8 percent of GDP in 1999.